Effect of carbon nanoparticle addition on epoxy cure - Dimopoulos, Athanasios (Cranfield University, 2007)
The thesis reports studies of cure kinetics and the glass transition temperature advancements of three commercial epoxy resin systems: MY 750 / HY 5922 (Vantico), MTM 44 -1 (ACG) and 8552 (Hexcel Composites). This investigation was conducted with the utilisation of Differential Scanning Calorimetry (DSC) and Temperature Modulated DSC (TMDSC). Appropriate phenomenological cure kinetics models were built to predict the degree of cure as a function of temperature/time profile. The validity of superposition of dynamic and isothermal experimental data was established. Rheological measurements were performed in order to determine the gelation region under given cure conditions. The cure modelling methodology was validated against an international Round-Robin exercise led by the University of British Columbia (Canada). The effects of carbon nanoparticle incorporation on the cure kinetics and the glass transition temperature advancement of two of the epoxy systems were also studied. Cure kinetics models were developed for the nanocomposites containing commercial multiwalled carbon nanotubes and a direct comparison was made with the models of the neat resin systems. The glass transition temperature advancement is shown to be affected in the early stages of the cure. The state of the dispersion of the nanoparticles was studied in order to correlate it with the observed effects upon the cure and on the morphology of the cured samples. The presence of carbon nanotube clusters is shown to have an influence on the phase separation in the MTM 44-1 resin system. As a potential industrial application of this study, optical fibre refractometers were utilised as an on-line cure monitoring technique. A good correlation was established between the measured refractive index changes during the cure and the degree of cure predicted by the above mentioned models, for the neat resin systems and their nanocomposites.